Market selection for international real estate investments - Falkenbach, Heidi (International Journal of Strategic Property Management, 2009)
This paper studies the market selection criteria in international real estate investments. It presents the results of a questionnaire study among internationally investing property investors in Europe. The results indicate that the most important factors for market selection are safety of property rights and title as well as expected return on property investments. Also other factors describing institutional set‐up and market maturity were found to affect the market selection process, whereas the correlation of the property returns was not found to have a large impact on market selection. First Publish Online: 18 Oct 2010